Nano-aluminum: Transport through sand columns and environmental effects on plants and soil communities - Doshi, Reeti; Braida, Washington; Christodoulatos, Christos; Wazne, Mahmoud; O’Connor, Gregory (Environmental research, 2008)
Nano-aluminum is being used in increasing quantities as energetic material. This research addresses the transport of two types of nanosized aluminum particles (with aluminum oxide, or carboxylate ligand coating, Alex and L-Alex, respectively) through sand columns along with associated environmental impacts on soil systems. Surface phenomena and pH are variables controlling the transport of nano-aluminum particles through porous media. pH environment controls solubility and electrostatic interactions between nano-aluminum particles and porous media. (i.e., changes in point of zero charge, agglomeration, etc.). Concentrations (up to 17 mg/L) far greater than the World Health Organization guideline for Al in drinking water (0.2 mg/L) were measured in columns’ leachates. Plant uptake studies, mineralization of radiolabeled glucose test and Microtox test were used to investigate the environmental impacts of nano-aluminum on soil communities and plants. It appears that the presence of nano-aluminum particles did not have an adverse effect on the growth of California red kidney bean ( Phaseolus vulgaris) and rye grass ( Lolium perenne) plants in the concentration range tested. California red beans did not show uptake of aluminum, while the situation was different for rye grass where a 2.5-fold increase in Al concentration in the leaves was observed as compared with control tests. Nano-aluminum particles in suspension do not appear to have an impact on the metabolic activity of Vibrio fischeri. However, when the nano-aluminum particles were amended to the soil, Alex aluminum resulted in a 50% reduction of light output at concentrations below 5000 mg/L soil suspension concentration while L-Alex showed a similar effect at around 17,500 mg/L and the control soil at 37,500 mg/L. Soil respiration studies show that there are not statistical differences between the time and sizes of peaks in CO 2 production and the total mineralization of glucose.